ADAPT FAST study: a direct aspiration first pass technique for acute stroke thrombectomy. (25th February 2014) - Turk, Aquilla S; Frei, Don; Fiorella, David; Mocco, J; Baxter, Blaise; Siddiqui, Adnan; Spiotta, Alex; Mokin, Maxim; Dewan, Michael; Quarfordt, Steve; Battenhouse, Holly; Turner, Raymond; et al.
Abstract : Background: The development of new revascularization devices has improved recanalization rates and time, but not clinical outcomes. We report a prospectively collected clinical experience with a new technique utilizing a direct aspiration first pass technique with large bore aspiration catheter as the primary method for vessel recanalization. Methods: 98 prospectively identified acute ischemic stroke patients with 100 occluded large cerebral vessels at six institutions were included in the study. The ADAPT technique was utilized in all patients. Procedural and clinical data were captured for analysis. Results: The aspiration component of the ADAPT technique alone was successful in achieving Thrombolysis in Cerebral Infarction (TICI) 2b or 3 revascularization in 78% of cases. The additional use of stent retrievers improved the TICI 2b/3 revascularization rate to 95%. The average time from groin puncture to at least TICI 2b recanalization was 37 min. A 5MAX demonstrated similar success to a 5MAX ACE in achieving TICI 2b/3 revascularization alone (75% vs 82%, p=0.43). Patients presented with an admitting median National Institutes of Health Stroke Scale (NIHSS) score of 17.0 (12.0–21.0) and improved to a median NIHSS score at discharge of 7.3 (1.0–11.0). Ninety day functional outcomes were 40% (modified Rankin Scale (mRS) 0–2) and 20% (mRS 6). There were two procedural complications and no symptomatic intracerebral hemorrhages. Discussion: The ADAPT technique is a fast, safe, simple, and effective method that has facilitated our approach to acute ischemic stroke thrombectomy by utilizing the latest generation of large bore aspiration catheters to achieve previously unparalleled angiographic outcomes.